Kontrol diri mahasiswa yang kecanduan game online di Asrama Kaway XVI - Khairiah Asfaruddin; Said Nurdin; Rezki Saifan (Jurnal Suloh, 2019)
Addicted to online games are harmful behaviors, dangerous and can even be classified into mental disorders that need to be avoided. Individuals who are addicted to online games are characterized by behavior unable to break away from thinking about games, neglecting work and not being able to control themselves which causes more intensity and duration of playing time and drains the mind. The study aims to describe the self-control of college students who have the characteristics of online game addicts employing a qualitative with descriptive approach. Research subjects were three teenagers who have the characteristics of online game addiction. Data collection techniques are done through interviews. The results showed that students were sometimes unable to control themselves, especially when playing online games. They will forget or rule out other things that need to be done. But there are times when students are able to avoid playing online games for example when there are class schedules and other assignments and jobs. Students are in the early period of adulthood; this was predicted what underlies the change of ability and inability to control themselves in playing online games. Keywords: Self-control, College Student, Game Online addiction ABSTRAK Kecanduan game online adalah perilaku yang merugikan, berbahaya bahkan dapat digolongkan ke dalam gangguan mental sehingga perlu dihindari. Individu yang mengalami kecanduan game online ditandai dengan perilaku selalu memikirkan game, mengabaikan pekerjaan, kehilangan kontrol diri, sehingga intensitas dan durasi bermain game semakin banyak. Penelitian ini bertujuan untuk mengetahui kontrol diri mahasiswa yang memiliki ciri pecandu game online dengan menggunakan pendekatan kualitatif deskriptif. Pengumpulan data dilakukan melalui wawancara dengan tiga orang mahasiswa yang memiliki ciri kecanduan game online. Hasil penelitian menunjukkan bahwa mahasiswa terkadang tidak mampu mengontrol dirinya terutama saat sedang bermain game online. Mereka akan melupakan atau mengesampingkan hal-hal lain yang perlu dikerjakan. Namun ada waktunya mahasiswa mampu menghindar dari bermain game online misalnya saat ada jadwal perkuliahan maupun tugas dan pekerjaan lain. Mahasiswa berada pada periode awal masa dewasa, ini yang diperkirakan mendasari adanya perubahan dari kemampuan dan ketidakmampuan mengontrol diri dalam bermain game online.   Kata Kunci: Kontrol Diri, Mahasiswa, Kecanduan Game Online